Impact of the estrous cycle on brain monoamines and behavioral and respiratory responses to CO2 in mice - Dominiquini-Moraes, Beatriz [UNESP]; Bernardes-Ribeiro, Mariana [UNESP]; Patrone, Luis Gustavo A. [UNESP]; Fonseca, Elisa M.; Frias, Alana T. [UNESP]; Silva, Kaoma S. Costa; Araujo-Lopes, Roberta; Szawka, Raphael E.; Bícego, Kênia C. [UNESP]; Zangrossi, Hélio; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2025)
The prevalence of panic disorder is two to four times higher in women compared to that in men, and hormonal changes during the menstrual cycle play a role in the occurrence of panic attacks. Here, we investigated the effect of the estrous cycle on the ventilatory and behavioral responses to CO2 in mice. Female mice in proestrus, estrus, metestrus, or diestrus were exposed to 20% CO2, and their escape behaviors, brain monoamines, and plasma levels of 17β-estradiol (E2) and progesterone (P4) were measured. Pulmonary ventilation (V̇E), oxygen consumption (V̇O2), and body core temperature (TB) were also measured during normocapnia followed by CO2. Females exposed to 20% CO2 exhibited an escape behavior, but the estrous cycle did not affect this response. Females in all phases of the estrous cycle showed higher V̇E and lower TB during hypercapnia. In diestrus, there was an attenuation of CO2-induced hyperventilation with no change in V̇O2, whereas in estrus, this response was accompanied by a reduction in V̇O2. Hypercapnia also increased the concentration of plasma P4 and central DOPAC, the main dopamine metabolite, in all females. There was an estrous cycle effect on brainstem serotonin, with females in estrus showing a higher concentration than females in the metestrus and diestrus phases. Therefore, our data suggest that hypercapnia induces panic-related behaviors and ventilatory changes that lead to an increase in P4 secretion in female mice, likely originating from the adrenals. The estrous cycle does not affect the behavioral response but interferes in the ventilatory and metabolic responses to CO2 in mice.
Keywords: Chemosensitivity; Estrogen; Female; Hypercapnia; Panic disorder; Progesterone